Theoretical solution and failure analysis of water pressure on lining of deep-buried non-circular hydraulic tunnel based on the equivalent hydraulic radius method. (June 2023) - Duan, Shuqian; Jiang, Xiqing; Jiang, Quan; Xiong, Jiecheng; Li, Chenyang
Highlights: A simplified analytical model based on equivalent hydraulic radius was proposed. The distribution law of seepage pressure of non-circular tunnel could be derived. Accuracy and superiority of the equivalent hydraulic radius method were verified. Parameters of each part of the composite lining were optimized. The failure of the lining before and after parameter optimization was analyzed. Abstract: The water pressure distribution acting on non-circular hydraulic tunnels have always been an important and crucial issue in deep-buried tunnels and caverns, due to its complexity, variability and potential threats to the stability of surrounding rock and the safety of lining structure. This research proposes an accurate axisymmetric analytical solution for water pressure and seepage discharge on the surface of surrounding rock, the lining and grouting circle under high external and internal water pressures, by introducing an equivalent hydraulic radius method in to seepage theory in fractured media. Then, the distribution law of seepage pressure within different distances from the tunnel wall is derived by theoretical analysis. The accuracy, superiority and applicability of the theoretical solution based on the equivalent hydraulic radius are verified sufficiently. The maximum errors of the theoretical solution are less than 15%, 18% and 5.98% respectively, when compared to the numerical solution, the in-situ water pressure monitoring data and the theoretical solution based on the conformal mapping. And the proposed theoretical solution is much closer to the numerical solution than the existing equivalent methods. Moreover, parameters of each part of the composite lining are optimized. Increasing 10% of the original of the permeability coefficient of the composite lining can maximally reduce the external water pressure, and the maximum principal stress and displacement of the composite lining can be effectively reduced by comparing the contour of the maximum principal stress and displacement before and after parameter optimization. Furthermore, by comparing the excavation damage zone distribution before and after parameter optimization, the shear failure occurring in the composite lining is significantly reduced, and the stability of the composite lining structure can be improved. The conclusions could provide important guiding theoretical value for the further study of water pressure distribution acting on non-circular hydraulic tunnels as well as for the correct grouting and drainage designs.